1995
DOI: 10.1146/annurev.publhealth.16.1.327
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Health Assessment 1994

Abstract: General health status and a broader concept of quality of life are discussed and methods of widely used surveys are reviewed. A consensus regarding the inclusion of measures of physical, mental, social, and role functioning and general health perceptions is noted for comprehensive assessments of health. A schematic of relationships among condition-specific and generic measures is presented along with results expected for objective and subjective measures of physical and mental dimensions of health. Suggestions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 24 publications
0
94
0
Order By: Relevance
“…The scores for these two increased after the third infusion (though only with a trend for role emotional). In factor analytic studies these two scales and mental health have been shown to be most responsive, when compared before and after recovery from depression [27] and change in the severity of depression [28]. The three scales with the most mental factor content are even found to be sensitive to interpersonal therapy, as well as drug treatment for depression [29].…”
Section: Discussionmentioning
confidence: 99%
“…The scores for these two increased after the third infusion (though only with a trend for role emotional). In factor analytic studies these two scales and mental health have been shown to be most responsive, when compared before and after recovery from depression [27] and change in the severity of depression [28]. The three scales with the most mental factor content are even found to be sensitive to interpersonal therapy, as well as drug treatment for depression [29].…”
Section: Discussionmentioning
confidence: 99%
“…This conceptual model makes important distinctions between domains of health and their operational definitions. Figure 1 portrays a specific-generic continuum [10][11][12], rather than a simple categorization of specific and generic concepts and measures. For example, as one moves from the left to the right, the measures change from being the most highly specific and objective clinical measures (box 1), to disease-specific symptoms (box 2), to specific measures of Health-related quality of life disease impact (box 3), and to generic measures that are applicable across chronic disease and treatment groups.…”
Section: Asthma Impact Surveymentioning
confidence: 99%
“…As a measure of the patient's perspective, HRQL represents the "functional effect of an illness and its consequent therapy upon a patient, as perceived by the patient" [8] with some agreement that HRQL consists of at least four broad domains: physical function, psychological state, social interaction, and symptoms [9,10]. These four domains are felt to address those aspects of a patient's experience most affected by health care interventions and which need to be assessed by clinicians and researchers [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These four domains are felt to address those aspects of a patient's experience most affected by health care interventions and which need to be assessed by clinicians and researchers [9,10].…”
Section: Introductionmentioning
confidence: 99%